A PPARγ transcriptional cascade directs adipose progenitor cell-niche interaction and niche expansion - Yuwei Jiang (Nature Portfolio, 2017)
Adipocyte progenitor cells (APCs) are found tethered to adipose tissue blood vessel walls and can differentiate into adipocytes. Here the authors show that PPARγ controls angiogenesis by stimulating APC–blood vessel interaction and retention via a transcriptional network that includes PDGFRβand VEGF.